Manajemen Komunikasi dan Negosiasi Pendidikan Islam Multikultural - Alawilhuda, Muhammad Alawilhuda (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2025)
Indonesia, as a multicultural country, faces significant challenges in the field of education, particularly in managing cultural, ethnic, linguistic, and religious diversity. In the context of Islamic education, this diversity is not only reflected in the backgrounds of students but also in the values upheld by all educational stakeholders. Therefore, effective managerial strategies are needed to manage communication and negotiation processes to create an inclusive, harmonious, and equitable learning environment. This article aims to comprehensively examine the role of communication and negotiation management in multicultural Islamic education through a literature review approach that analyzes various relevant scholarly works. The findings reveal that effective multicultural communication requires openness, empathy, cultural awareness, and adaptability in interactions among individuals from diverse backgrounds. Barriers such as prejudice, stereotypes, ethnocentrism, and perceptual differences often hinder communication processes. Thus, negotiation becomes a key skill to bridge differences and reach fair agreements. In Islamic education, negotiation management based on the principles of justice, equality, mutual interest, and a win-win approach is essential for formulating inclusive policies and fostering constructive interactions. Furthermore, this article highlights the importance of managerial competence for Islamic education leaders as facilitators of intercultural dialogue and agents of change in creating educational spaces responsive to diversity. By emphasizing effective communication and negotiation management, Islamic educational institutions are expected to serve not only as centers of academic learning but also as platforms for nurturing social character that is tolerant, open-minded, and prepared to live in a pluralistic global society.